Pipeline Transport in the Context of International Law - Octay F. Efendiev (Московский журнал международного права, 2016)
The article examines the legal problems of elaboration of the new international economic world order within the transport sphere, with the accent to the growing role of pipe lines systems of transportation. It is stressed that in the regulation of systems the important meaning belongs to the question of harmonization of national and international legal norms and principles. This presupposes the adoption of the new as well as developing the acting legislation including the sphere of regulation of obligatory technical-economic demands of safety of various kinds of pipe lines with the view of national peculiarities.